The Story “Alyosha the Pot” by Leo Tolstoy: Interpretation Experience - Irina B. Pavlova (Два века русской классики, 2025)
The article is devoted to the artistic realization of the theme of the confrontation between good and evil in the story “Alyosha the Pot” (1905) by Leo Tolstoy on the metaphysical, socio-psychological, historical, and ethical levels. The hero of the work, genetically associated with folklore, combines humility, non-resistance to evil, love for one’s neighbors, and a timid awakening of the personal principle. The researcher focuses on the image of the “pot,” associated with biblical and folklore traditions, which is the semantic core of the story, and the image of the “father-master,” acting as an intermediary in the spread of evil. The article analyzes the functions of such artistic details as ice, and iron boots, symbolic of the fate of Alyosha the Pot. The author examines the phenomenon of thirst and surprise, which acquires metaphysical significance, which is characteristic of Tolstoy’s late works when it comes to good and evil, life and death, and man’s relationship with eternity. The story embodies the writer’s ideological contradictions, his desire for his own interpretation of the Holy Scripture, and an apology for the idea of non-resistance. According to the internal logic of the artistic text, the image of the “father-master” is debunked, and Alyosha Gorshok has come closer to the mystery of eternal life. The apotheosis of the story is the depiction of the inescapable confrontation between good and evil in the world.